Design of multipoint coal flow monitoring system of belt conveyor based on ultrasonic - CHEN Xiangyua (Gong-kuang zidonghua, 2017)
In view of problem that it is difficult to accurately measure instantaneous coal flow of mine-used belt conveyor with high speed and large capacity, a multipoint coal flow monitoring system of belt conveyor based on ultrasonic was designed, design of hardware, software and coal flow detection algorithm of the system were introduced. The system uses ultrasonic sensor and speed sensor to obtain parameters information such as coal height, coal pile area and speed rate of belt under high speed running of belt conveyor, the data was fit and analyzed by coal flow detection algorithm, so as to calculate coal flow. The test results show that the system can accurately measure coal flow of belt conveyer, measurement accuracy is up to 91%.